Identification and characterization of Burkholderia multivorans CCA53 - Akita, Hironaga; Kimura, Zen-ichiro; Mohd Yusoff, Mohd Zulkhairi; Nakashima, Nobutaka; Hoshino, Tamotsu (BioMed Central, 2017)
Objective: A lignin-degrading bacterium, Burkholderia sp. CCA53, was previously isolated from leaf soil. The purpose of this study was to determine phenotypic and biochemical features of Burkholderia sp. CCA53. Results: Multilocus sequence typing (MLST) analysis based on fragments of the atpD, gltD, gyrB, lepA, recA and trpB gene sequences was performed to identify Burkholderia sp. CCA53. The MLST analysis revealed that Burkholderia sp. CCA53 was tightly clustered with B. multivorans ATCC BAA-247T. The quinone and cellular fatty acid profiles, carbon source utilization, growth temperature and pH were consistent with the characteristics of B. multivorans species. Burkholderia sp. CCA53 was therefore identified as B. multivorans CCA53.